Effects of faecal residues of moxidectin and doramectin on the activity of arthropods in cattle dung - Suarez, Víctor Humberto (2009)
Dung invertebrate colonization and degradation levels of faeces from cattle treated with endectocides were studied. Faeces of control and doramectin (DRM) (subcutaneous) and moxidectin (MXD) (subcutaneous and topical) treated animals were deposited on the field from 3 to 21 days post-treatment (pt). Pats were recovered after 6 to 42 days post-deposition (pd). Faecal weight, dry matter, arthropods number, and drugs concentrations were determined. Total arthropods number was higher in control (P<0.0001) than in the other groups from days 3 to 21 pt. Total number of insects recovered on days 3, 11, and 21 pt from control pats was significantly (P<0.001) higher than in treated-animal pats during all the trial. At day 21 pt, the insects' number in dung voided by DRM-treated cattle was (P<0.05) lower than in the other groups. Comparisons of dung degradation among treatments were inconclusive. A lower adverse effect was observed for MXD compared with DRM. No significant degradation of MXD or DRM was observed during the present trial.